The relationship between wives' estimates of time spent doing housework, support and wives' well-being - Noor, Noraini M. (John Wiley & Sons, Ltd., 1997)
This study examines the relationship between the distribution of labour at home and employed women's psychological distress. The distribution of labour at home is measured by wives' estimates of their own and their husbands' time spent doing housework. It is hypothesized that what is more important to women's well-being is their estimates of their husbands' time spent doing housework rather than their own time. It is further hypothesized that one pathway in which wives' estimates of husbands' time spent doing housework influences their well-being is through perceptions of support. In a sample of 153 employed married women, using regression analyses, results are consistent with the predictions made. First, wives' estimates of their husbands' time spent doing housework is a better predictor of their well-being than their estimates of their own time spent. Second, support acts as a partial mediator in this relationship. These findings are discussed with respect to recent work in the area.